Comparative study of sample preparation procedures to determine the main compounds in ayahuasca beverages by QuEChERS and high‐performance liquid chromatography analysis - Gonçalves, Joana (2024)
Introduction : Ayahuasca is a psychoactive drink originally consumed by indigenous people of the Amazon. The lack of regulation of this drink leads to uncontrolled consumption, and it is often consumed in religious contexts. Objective :The aim of this work is to compare three miniaturised extraction techniques for extracting the main ayahuasca compounds from beverages. Methodology:Three sample pretreatment techniques were evaluated (dispersive liquid–liquid microextraction [DLLME], microextraction by packed sorbent [MEPS] and QuEChERS [Quick, Easy, Cheap, Effective, Rugged and Safe]) for the simultaneous extraction of N,N-dimethyltryptamine (DMT), tetrahydroharmine (THH), harmine, harmaline, harmol and harmalol from ayahuasca beverage samples. Then, the most promising technique (QuEChERS) was chosen to pre-concentrate the analytes, subsequently detected by high-performance liquid chromatography coupled to a diode array detector (HPLC-DAD). Results: The procedure was optimised, with the final conditions being 500 μL of extractor solvent, 85 mg of primary secondary amine (PSA) and 4 s of vortexing. The analytical method was validated, showing to be linear between 0.16 and 10 μg/mL for β-carbolines and between 0.016 and 1 μg/mL for DMT, with coefficients of determination (R2) between 0.9968 and 0.9993. The limit of detection (LOD) and lower limit of quantification (LLOQ) were 0.16 μg/mL for all compounds, except for DMT (0.016 μg/mL) and extraction efficiencies varied between 60.2% and 88.0%. Conclusion: The analytical methodology proved to be accurate and precise, with good linearity, LODs and LLOQs. This method has been fully validated and successfully applied to ayahuasca beverage samples.